Arabic and Islamic Studies Teachers and Career Problems in Nigeria - Ahmad Garba (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Arabic language its teachers and intellectuals have been facing difficulties and obstacles for a long time in Nigeria, and these difficulties are often related to their profession, Unfortunately, this language has encountered obstacles that impede its tremendous growth and development, Professional problems are among the most challenges facing many teachers of Arabic and Islamic studies in the country. These challenges started from the Nigerian educational policy, where the Arabic language was placed in third place among the foreign languages used in the country, despite the large number of Muslims and those interested in the Arabic language, This is due to the lackadasical attitude of government towards Arabic and Islamic studies teachers, and for this reason it is difficult for them to compete side by side with their counterparts from other fields in terms of professional development. On that basis, this paper aims to discuss the professional problems and obstacles bedeviling Arabic and Islamic studies teachers in Nigeria, and also intends to bring forward some solutions and way forward to that obstacles.